Solvent-free aminocarbonylation of iodobenzene in the presence of SILP-palladium catalysts. Issue 51 (9th May 2016) - Papp, M.; Szabó, P.; Srankó, D.; Skoda-Földes, R.
Abstract : The recyclable palladium catalysts were used for selective mono- or double carbonylation under solvent-free conditions and in DMF, respectively. Abstract : Heterogeneous palladium catalysts were prepared by the immobilisation of palladium on supported ionic liquid phases (SILP) obtained by physisorption or grafting. They were characterised by different techniques such as 13 C CP MAS NMR, 31 P CP MAS NMR, FT-IR, XPS and ICP. The catalysts were used efficiently under solvent-free conditions. They led to the formation of amide products with good to excellent selectivity. Recyclability at 5–10 bar CO pressure has also been demonstrated. The same reusable catalysts were proved to lead to the selective formation of double carbonylation products under higher pressure in DMF.